STRATEGI PENGEMBANGAN KEUANGAN SYARIAH DALAM MEWUJUDKAN KEADILAN SOSIAL-EKONOMI - Hamdani Hamdani (Fakultas Ekonomi Bisnis Islam, 2022)
Poverty and economic injustice are classic problems that have never been resolved, especially after the outbreak of Covid-19. The economic burden of low-income communities really needs government assistance in economic recovery. Social assistance in the form of Direct Cash Assistance (BLT), BIP scholarships and educational operational assistance cannot actually solve this problem. The role of private financial institutions, both Islamic banks and non-Islamic banking institutions, has contributed to national economic growth and reduced the poverty rate, which is 16% of the national figure. Islamic finance is an alternative solution to problems in increasing economic growth and increasing the fairness of economic distribution to low-income people. This study uses descriptive qualitative methods, with the aim of developing strategies for Islamic finance and social justice for the community to provide economic improvements for the community. The location of this research is Baitul Maal wa Tamwil (BMT) Nurul Ummah, Ngasem District, Bojonegoro Regency, East Java. BMT Nurul Ummah Ngasem as an Islamic microfinance institution and the development of Islamic social finance has been proven to empower the community's economy with various achievements. So this research produces the first conclusions about Islamic finance conducted by BMT Nurul Ummah Ngasem Bojonegoro who have carried out education, empowerment and community economic development through savings and financing methods for members of the BMT cooperative and also community assistance programs, secondly, BMT Nurul Ummah has conducted resource training human resources with the BMT Ngasem Institute program engaged in business training, HR clinics and entrepreneurship training. With this program, BMT Nurul Ummah is a role model for BMT that should be emulated